The efficacy of acupuncture for attention deficit hyperactivity disorder (ADHD): An overview of systematic reviews and meta-analyses - Lulu Zhang; Chuyu Huang; Xinying Chen; Shujuan Du; Jinghua Yang; Binwen Hu (Elsevier, 2023)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most common neurological and mental developmental disorders in children. Published systematic reviews (SRs) and meta-analyses (MAs) concerning the use of acupuncture for ADHD have compared the efficacy of acupuncture treatment to that of drug therapies. However, the quality of these articles has not been evaluated and the evidence varies widely. Objective: To summarize and assess the efficacy of acupuncture for ADHD based on existing SRs and MAs. Methods: A systematic search of the literature was conducted from inception until September 16 2021, using seven electronic databases. The AMSTAR-2 tool was used to evaluate the quality of SRs and MAs, and the GRADE system was used to assess the quality of evidence. Results: There are a total of five SRs and MAs included in this overview. Using the AMSTAR-2, three articles were rated as having 'Low' quality, while two were rated as having of 'Critically Low' quality. The GRADE system was used to measure the quality of evidence for ten outcomes (five response rate outcomes, three Conners' Index of Hyperactivity (CIH) score outcomes, one Conners' rating scale score outcome, and one Chinese medicine syndrome outcome) across the five included MAs. Four of the ten outcomes demonstrated 'moderate' quality, four demonstrated 'low' quality, and two demonstrated 'very low' quality. The risk of bias and inconsistency accounted for most downgrading factors in the included reviews. Conclusion: It is still debatable whether acupuncture is efficacious in improving the CIH score and the Response rate. Considering the heterogeneity of clinical trials and the fact that this study did not search and evaluate the relevant data of each randomized controlled trial, large-sample and high-quality randomized controlled trials are still needed to draw reliable conclusions regarding acupuncture's role in treating ADHD. Due to the poor quality of existing available evidence, little inference can be drawn from the included studies.